Significant Relationship Between Family Conflict and the Implications of Students Who Are Frequently Bullied at School - Mutia Qana'a; Prihantini; Tin Rustini; Pikir Wisnu Wijayanto (LPPM Undiksha, 2024)
Bullying is a problem that often occurs in schools. Facts show that students who often carry out bullying come from less harmonious family backgrounds. This is urgent to research with the aim of analyzing the relationship between family conflict and the stages of bullying in male students in middle school. Quantitative research method. The subjects were students with a population of 450 people and only 76 students had bullying tendencies. These 76 students were selected as samples in this study. Data collection techniques using instruments. Question instrument to investigate the Bullying Behavior Stage. Family Conflict Violence Investigation is used to measure students' stages of family conflict. Measurement with a Likert scale of 1-5. Descriptive statistical analysis techniques and inference statistics (Pearson correlation test). The results and findings show that the level of bullying among male students tends to be at a low level (2.52). A significant relationship was found between family conflict and stages of bullying. It was found that the frequency of conflict was minimal for the type of sibling conflict within students at school and the most frequent conflict was between parents and students. The findings show that family conflict factors need to receive serious attention and be taken into account in designing intervention programs to prevent the bullying phenomenon from becoming more serious in schools.